Acute toxicity of the galactagogue phytomedicine containing Sauropus androgynous, Trigonella foenum-graecum, and Moringa oleifera - Zulkhah Noor; Zulkhah Noor; Dwi Liliek Kusindarta; Ahmad Hamim Sadewa; Didik Setyo Heriyanto; Diah Rumekti Hadiati; Mustofa (Faculty of Pharmacy, Mahidol University, 2022)
This study aims to evaluate acute toxicity of the herbal preparation on rats as an early step to evaluate its safety. This study used 25 females Rattus norvegicus strain Sprague Dawley rats aged 8 weeks with a body weight of at least 120 g divided into 5 groups of doses of herbal preparation (0/aquadest, 50, 300, 2,000, 5,000) mg/kg BW. After administration of the herbal preparation, rats were observed using a camera continuously for 14 days and manual observation intensively for the first 24 hours and then once a day for up to 14 days. The toxic effects including death, behavioral changes, neural symptoms, and other abnormalitieswere recorded. The weight of the rats was monitored every three days. On the 15th day, the rats were sacrificed to collect vital organs for macroscopic and histopathological examinations. The LD50 was estimated based on OECD Guideline. No mortality and significant toxicity signs in any of the rats after receiving the herbal formula at highest dose of 5000 mg/kg was reported during the 14-day observation period. Bodyweight and organ weight did not show significant variation between controls and treatment groups. In addition, no abnormalities of liver, heart and lungs were also observed in macroscopic and histopathological examinations. In conclusion, the herbal preparation shows the LD50 of greater than 5,000 mg/kg can be classified as category 5 or unclassified. Further sub chronic toxicity study will be conducted to evaluate its safety after repeated exposure.